2016
DOI: 10.17576/jkmjc-2016-3201-18
|View full text |Cite
|
Sign up to set email alerts
|

“YouTube” dan Generasi Muda Islam: Satu Pendekatan Kelompok Fokus dalam Kalangan Pelajar Universiti (“YouTube” and The Young Muslim Generation: A Focus Group Approach Among University Students)

Abstract: Kehadiran "YouTube" hari ini memberikan ruang generasi muda Islam mencari maklumat agama dalam "YouTube". Pencarian maklumat ini memberi persepsi kepercayaan yang berlainan kepada generasi muda ini terutama kelahiran maklumat 'Ustaz YouTube' yang menyampaikan maklumat agama yang tidak pasti kesahihan maklumat tersebut. Objektif kertas kerja ini adalah untuk mengenal pasti jenis maklumat agama yang dilayari dalam "YouTube" dan mengenal pasti persepsi kepercayaan "YouTube" sebagai sumber maklumat agama. Kajian i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, the condition still bears both positive and negative impacts (Neumann and Herodotou, 2020). It was found that youths and informants surf Youtube for information from educative and entertaining videos (Aguslianto, 2017;Aripin et al, 2016;Pires et al, 2019).…”
Section: Youtube and The Young Generationmentioning
confidence: 99%
“…However, the condition still bears both positive and negative impacts (Neumann and Herodotou, 2020). It was found that youths and informants surf Youtube for information from educative and entertaining videos (Aguslianto, 2017;Aripin et al, 2016;Pires et al, 2019).…”
Section: Youtube and The Young Generationmentioning
confidence: 99%
“…Access to social media networks may enable students to trust that they have the chances to get help from many sources through the sites even though the sites are not explicitly used for academic purposes [18] [19] [20]. [21] stated that social media networking also can possibly be utilized in a learning situation as it advances psychological commitment of students in class and along these lines their scholarly execution and achievement.…”
Section: Social Media and Language Learningmentioning
confidence: 99%